PENDIDIKAN KARAKTER ANAK DALAM CERITA KANCIL DAN SIPUT (SERI CERITA RAKYAT DAYAK KANAYATN KALIMANTAN BARAT) - Binar Kurniasari Febrianti (tuahtalino, 2017)
Nowadays character is often echoed in the world of education which focused on children's education. The purpose of character education is expected to develop children's personal character and virtuous character better that is manifested in everyday behavior. Folklore is part of the literature included in the teaching materials could be a source of character education. Folklore is stories told and developed in the community from generation to generation in their respective regions in the archipelago. Likewise in West Kalimantan which is populated by ethnic Malay, Dayak, Chinese, Bugis, Madurese and Javanese has the folklore of their respective ethnic groups, one of them is Dayak Kanayatn folklore. Folklore which is read by children could affect the children’s character in everyday life. Folklore contains not only education, but also rich in cultural values and moral values as character education purpose—that is building the children’s character through the lessons. The aim of this paper is to reveal and analyze the children’s character education in Cerita Kancil dan Siput (Tale of Hare and Snail). The writing object is the text of Tale of Hare and Snail contained in the book series entitled Kalbar Folklore of The Tortoise and Companions. The method used is descriptive and technical literature. This paper analyzes the contents of children’s character in Tale of Hare and Snail. The results of this paper is folklore Dayak Kanayatn titled Tale of Hare and Snail contains character education which also exists in the nine pillars of character education in Indonesia. It is expected that more local folklore which could be medium of teaching materials containing noble values of the local community would build children’s personal positive, great and amazing.